2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009482
|View full text |Cite
|
Sign up to set email alerts
|

CRUX: A compliant robotic upper-extremity exosuit for lightweight, portable, multi-joint muscular augmentation

Abstract: Wearable robots can potentially offer their users enhanced stability and strength. These augmentations are ideally designed to actuate harmoniously with the user's movements and provide extra force as needed. The creation of such robots, however, is particularly challenging due to the underlying complexity of the human body. In this paper, we present a compliant, robotic exosuit for upper extremities called CRUX. This exosuit, inspired by tensegrity models of the human arm, features a lightweight (1.3 kg), fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…This category of exoskeletons is designed to assist the user in motion amplification or augmentation, where it can be used to assist the users for motion amplification [7,[30][31][32][33][34][35][36][37]; helps to reduce the burden while working in a harsh industrial environment [38,39]; or supplements the physically weak individuals in their activities of daily living. So far, many new systems have been developed and tested during past few years.…”
Section: Exoskeletons For Motion Assistancementioning
confidence: 99%
See 1 more Smart Citation
“…This category of exoskeletons is designed to assist the user in motion amplification or augmentation, where it can be used to assist the users for motion amplification [7,[30][31][32][33][34][35][36][37]; helps to reduce the burden while working in a harsh industrial environment [38,39]; or supplements the physically weak individuals in their activities of daily living. So far, many new systems have been developed and tested during past few years.…”
Section: Exoskeletons For Motion Assistancementioning
confidence: 99%
“…Lessard et al [31] proposed a soft exosuit for upper-limb rehabilitation, shown in Figure 3B. The study has identified the drawback of classical rigid body exoskeletons and their inability to comply with natural human body movements in a flexible way [62].…”
Section: Compliant Robotic Upper-extremity Exosuit (Crux)mentioning
confidence: 99%
“…Of these devices, four used gyroscopes, 19,25,29,41 five used accelerometers, 16,19,28,37,41 one used magnetometers, 41 and one used an unspecified IMU. 18 Six of the systems collect elbow data, 16,18,19,25,28,29 two collect shoulder data, 16,18 one collects wrist data, 41 and two measure hand data using IMUs. 16,41 IMUs are generally inexpensive, compact and have a wide breadth of possible applications.…”
Section: Electric Motormentioning
confidence: 99%
“…used brushless DC motors, 17,19,23,24,28,31,41,58 6% used both brush and brushless DC motors, 21,29 and 28% do not specify the type of DC motor that is used. Rotational motion is provided by 82% 11,[17][18][19][21][22][23][24]28,29,31,33,34,40,43,47,[49][50][51][52][53][58][59][60]62,63,65,69 of these DC motors and the remaining 18% provide linear motion. 36,46,54,55,66,70 The rotational DC motors all require a gearhead to increase the torque output, which is transmitted to the required joint through either cables, Bowden cables, gears, or linkages.…”
Section: %mentioning
confidence: 99%
“…* The authors are with The Hamlyn Centre, Department of Computing, Institute for Global Health Innovation, Imperial College London, SW7 2AZ, London, UK (email: r.varghese15@imperial.ac.uk) cussed on 1-DoF (abduction/adduction) assistance for the shoulder [7,8]. 2-DoF solutions include a semi-rigid continuum robot system [9] and two multi-DoF tendon-driven exosuits [10,11].…”
Section: Introductionmentioning
confidence: 99%